Chile - Financial Sector Assessment Program : Digital Financial Inclusion - Cohen, Charles (World Bank, Washington, DC, 2022)
Chile has achieved high levels of financial inclusion relative to its level of economic development across a number of headline indicators. Unlike in other countries, gaps in account ownership between men and women, rich and poor, older and younger consumers, and rural consumers are not pronounced. Remaining challenges in financial inclusion include pockets of underserved segments and opportunities to further increase in online payments and digital financial services (DFS). There is also opportunity to improve the availability of savings, credit, and account products that are appropriately tailored to meet the needs of underserved consumers. Greater digitalization of the financial sector can help Chile to address some of the remaining challenges for financial inclusion in Chile. Several key elements of a well-functioning DFS ecosystem could be strengthened. At a broader level, the Fintech Bill should be passed to allow for greater innovation and competition in the financial sector. A range of opportunities exist to build off of Chile’s relatively advanced national payments infrastructure to help further expand in low-value retail payments and digital payments. There are indications that interest rate caps have inadvertently constrained access to finance for Chilean microenterprises. Legal and regulatory reforms could be considered to encourage microsavings. Banco Estado has played a huge role in advancing financial inclusion in Chile. To move to the next stage of financial inclusion, it is recommended that a national financial inclusion strategy (NFIS) be developed that is holistic and comprehensive.